Planetary health in the tropics: how community health-care doubles as a conservation tool - Kinari Webb (Elsevier, 2018)
Background: The Indonesian non-profit organisation Alam Sehat Lestari (ASRI), with support from the US non-profit organisation Health In Harmony, was created in 2007 to protect biodiverse rainforest in Gunung Palung National Park (GPNP) in Borneo, Indonesia, and to improve the lives of the communities surrounding the park. ASRI used a process of radical listening to identify the drivers of deforestation within the park and to help the community design and execute solutions. Methods: Based on community design, multiple strategies relating to health service provision and alternative livelihoods training were implemented. To understand the health and conservation changes in the project communities, we did three quantitative surveys of 25 villages surrounding GPNP: one in 2007 (baseline), one in 2012 (5 years), and one in 2017 (10 years). Pairs of trained nurses systematically interviewed 1300 households out of 60 000 in the region. Additionally, to assess how the project was working, a qualitative study using realist methodology was selected to help determine whether there were aspects of ASRI's multipronged approach that the communities saw as effective in motivating conservation behaviour, and under what circumstances the model might be replicable in other areas of high-conservation value under threat by local communities. 70 interviews were conducted among loggers, patients, government officials, and random community members. Findings: The quantitative results demonstrated that positive changes were being achieved, with a 68% drop by 2012 and a 89% drop by 2017 in households practising illegal logging (a decrease from an estimated 1350 logging households to 150 logging households currently) and a concomitant stabilisation of primary forest loss. By 2012, infant mortality decreased from 3·2 per 100 households to 1·1 per 100 households (70% decrease). The qualitative survey indicated that social capital and female empowerment played an important part in the positive community responses to the project's conservation messaging. Interpretation: Health In Harmony and the ASRI clinic have improved the health of the people and of the forest in the GPNP region in Borneo. This comprehensive approach to conservation and health care provides innovative solutions to conserving the environment while empowering individuals to improve the health of their communities. Funding: None.